Ethical and Corporate Governance Challenges that Rocked the Zimbabwean Financial Sector Between 2003- 2008 - Costain Mukanganiki; Gabriel Maibvisira; Precious Kandufu (International Journals Of Multidisciplinary Research Academy, 2022)
The purpose of this paper was to discuss the ethical and corporate governance challenges that rocked the Zimbabwean financial sector between 2003-2008. The paper has also evaluated the measures that were taken by the Reserve Bank of Zimbabwe (RBZ) to try and address the challenges. It also explored whether the measures were sufficient in nature and adequate in degree. The research adopted the case study design by citing cases of financial institutions which collapsed or faced near closure due to the numerous corporate lapses experienced in the sector. Data collection was through desk research and analysis was qualitative judgmental sampling and this was used to select all the cases cited in this paper. Findings clearly indicated that in all cases where ethical and corporate governance challenges were highly reflected, either the chief executive officer or chairman wielded disproportionate power in the board. This unfettered power rose from major shareholding which overshadowed the significance of other directors in the institutions. It came out clear that after liberalisation of the sector in the 1990s, an environment was created in which the Zimbabwean financial services industry could thrive, and where excessive risk taking and an adventurous business culture was embraced. Not only was this embraced by government, and industry, Zimbabwean society as a whole also participated. The measures taken by the central bank were a welcome development despite them being sort of voluntary. The way (forceful in nature) through which the central bank engaged in reigning in offenders was necessary at the time.